2010
DOI: 10.1021/jp911731s
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Morphology and Structure of Nanosized Zn2SiO4: Mn2+ Phosphors Using the Hydrothermal Method and Their Luminescence Properties

Abstract: Mn2+-doped Zn2SiO4 phosphors with nanoellipsoid or nanowire morphologies were synthesized at low temperature <200 °C by a hydrothermal method without any surfactants. The morphologies of the phosphors were easily tailored by varying the amount of hydroxide ions in the precursor solution before the hydrothermal reaction. Absolute ethanol was used as a solvent instead of distilled water to explore the effects of hydroxide ions on the morphology and crystal structure. We adjusted the amount of hydroxide ions by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Similarly, the particle size of the willemite produced by Al–nidawi et al [36] were at the range between 500–1000 nm, and this involved high temperature up to 1400 °C. The willemite NPs synthesized by hydrothermal methods generally involves low calcination temperature between 200–700 °C [37,38,39]. For instance, Zeng et al [37] synthesized non–uniformly distributed particles of willemite sized between 200–300 nm at the sintering conditions of 230 °C for 12 h. The same procedure was used by Xu et al [40].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the particle size of the willemite produced by Al–nidawi et al [36] were at the range between 500–1000 nm, and this involved high temperature up to 1400 °C. The willemite NPs synthesized by hydrothermal methods generally involves low calcination temperature between 200–700 °C [37,38,39]. For instance, Zeng et al [37] synthesized non–uniformly distributed particles of willemite sized between 200–300 nm at the sintering conditions of 230 °C for 12 h. The same procedure was used by Xu et al [40].…”
Section: Introductionmentioning
confidence: 99%
“…Willemite Zn 2 SiO 4 is a natural orthosilicate with a phenacite-like structure in which ZnAO tetrahedra and SiAO tetrahedra share corners to form hollow 'tubes' parallel to [0 0 0 1] [17,18]. The numerous investigations on the synthesis routes of Zn 2 SiO 4 have been carried out, including sol-gel method [19], solid-state route [20], polymer precursor method [21], spray pyrolysis method [22] and hydrothermal method [23,24]. However these methods usually require high pressure or heat-treating at temperatures higher than 180°C for several hours.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ., reported that ZSO firstly formed in the hydrothermal procedure, then ZSO would transform to ZS if it had a higher temperature or a longer reaction time in this step. An et al., suggested that ZSO tended to form at a higher pH value, and ZS would form at relatively low pH value (7 or 9) because of the deficiency of the hydroxide ions. However, our study indicates that the reactant concentration plays a significant role in the phase of final products.…”
Section: Resultsmentioning
confidence: 99%